The Role of Bahtsul Masail-Based Learning in Fiqh Lessons at Miftahul Huda 459 Rancabolang Garut Islamic Boarding School - Azizah, Dalfa; Rahmat, Acep; Saifullah, Iman (-, 2025)
This study aims to understand the role of Bahtsul Masail-based learning in Fiqh lessons at Miftahul Huda 459 Rancabolang Islamic Boarding School, Garut. Using a qualitative method with a case study design, this study involved students, kiai, and boarding school administrators as research subjects selected by purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed by data reduction, data presentation, and verification using source triangulation. The results of the study indicate that Bahtsul Masail-based learning plays a role in encouraging students to think critically, analytically, and argumentatively in understanding Islamic law. Discussions based on classical books conducted collectively help students connect fiqh theory with contemporary problems. The application of Bahtsul Masail in this Islamic boarding school uses the qauli, ilhaqi, and manhaji approaches, and involves intensive deliberations that improve students' understanding of fiqh. Learning evaluation is carried out through student involvement in discussions and preparation of materials before the session takes place.